Multimodal impressions of voice quality settings: the role of vocal and visual symbolism - Madureira, Sandra; Fontes, Mario A. S. (Frontiers in Communication, 2023)
This paper considers instances of voice quality settings under a sound-symbolic and synesthetic perspective, focusing on the auditory impressions these settings might have on listeners´ attributions of meaning effects and associations between vocal and visual features related to emotion expression. Three perceptual experiments are carried out. The first experiment examined the impressionistic effects of eight voice quality settings characterized by differences in pitch. The second experiment examined the impressionistic effects of seven voice quality settings characterized by productions with the presence or absence of turbulent airflow, irregularity, and tenseness. The third experiment investigated associations between facial expressions of basic emotions and voice quality characteristics. Data are considered in terms of acoustic (fundamental frequency values), articulatory (reduced or expanded length of the vocal tract), perceptual impressions of size (big/small), strength (strong/weak), brightness (dark, clear), and distinctiveness (muffled/distinct) and visual features (facial expressions of the basic emotions sadness, happiness, anger, disgust, fear, and neutrality). The results provide corroborating evidence of existing links between sound and meaning and are discussed in relation to the Frequency, Production, and Sirenic biological codes, phonetic metaphors, and the vocal and facial gestures involved in emotion expression.